Sustainable smart cities: the European case - Nevado Gil, T.; Pache Durán, M.; Carvalho, L.; Paiva, I. (Holistic approach for decision making towards designing smart cities, 2021)
Smart cities are emerging all over the world and are a promise to combat various problems currently faced by cities. This context makes smart cities a relevant topic for research. This study aims to identify which factors influence the development of sustainable smart cities. The empirical study uses a sample with 73 European cities and applies a multiple linear regression. The results suggest differences between smart cities in Europe, such as smarter cities are located geographically in the western region and are governed by women. This study provides an academic and empirical study on smart cities and contributes to a better explanation of a still under explored theme.